Compact freeform near-eye display system design enabled by optical-digital joint optimization - Xu, Huiming; Yang, Tong; Cheng, Dewen; Wang, Yongtian (Frontiers in Physics, 2024)
The near-eye display (NED) systems, designed to project content into the human eye, are pivotal in the realms of augmented reality (AR) and virtual reality (VR), offering users immersive experiences. Small volume is the key for fashion, easy-to-wear, comfortable NED system for industrial and consumer use. Freeform surfaces can significantly reduce system volume and weight while improving the system specifications. However, great challenges still exist in further reducing the volume of near-eye display systems as there is also a limit when using only freeform optics. This paper introduces a novel method for designing compact freeform NED systems through powerful optical-digital joint design. The method integrates geometrical freeform optical design with deep-learning of image compensation neural network, addressing off-axis nonsymmetric structures with complex freeform surfaces. A design example is presented to demonstrate the effectiveness of the proposed method. Specifically, the volume of a freeform NED system is reduced by approximately 63% compared to the system designed by traditional method, while still maintaining high-quality display performance. The proposed method opens a new pathway for the design of next generation ultra-compact NED system.